PERANCANGAN APLIKASI “BAGI BAGASI” DENGAN MENGGUNAKAN WEB DAN MOBILE - Ferdian Sugiarto; Desi Arisandi; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Service Application for Baggage using Mobile and Web is an application created aimed at making it easier for people to buy the needs of the community that are abroad or domestically. Often when traveling, we have excess baggage, from there BagiBagasi will help find potential buyers or prospective sellers and entrust the transaction process in this application. This application was designed using PHP and Android programming languages. The application design method uses the System Development Life Cycle. The test results are performed using the User Acceptance Test method and user satisfaction testing using the questionnaire method. With this application, the community is expected to be helped in meeting their needs for goods that cannot be bought by themselves.